Capital Structure and Its Effects on Firm Performance and Value: Evidence from Non-Financial Firms in Southeast Asia - Lestari, Ayu; Ichsanti, Novinda Kurnia; Ningsih, Sri (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This research investigates the impact of capital structure on the performance and value of non-financial firms listed in Southeast Asia. Capital structure is represented by the Debt to Equity Ratio (DER) and the Debt to Asset Ratio (DAR), while performance and value are evaluated through Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q. By utilizing secondary data sourced from the OSIRIS database covering the period from 2019 to 2023, the study employs panel data regression methods to analyze the proposed relationships. The findings reveal that DER significantly negatively affects ROA, suggesting that high levels of debt may impair asset efficiency. Conversely, DER does not have a significant effect on ROE or Tobin’s Q. On the other hand, DAR exhibits a positive and significant correlation with ROE, indicating that leverage can be advantageous when managed properly, although its impact on ROA and firm value is not statistically significant.